Covariation of psychobiological stress regulation with valence and quantity of social interactions in everyday life: disentangling intra- and interindividual sources of variation - Stoffel, Martin; Abbruzzese, Elvira A.; Rahn, Stefanie; Bossmann, Ulrike; Moessner, Markus; Ditzen, Beate (Journal of neural transmission, 2021)
While the overall effects of social relationships on stress and health have extensively been described, it remains unclear how the experience of social interactions covaries with the activity of psychobiological stress in everyday life. We hypothesized that the valence as well as quantitative characteristics of social interactions in everyday life would attenuate psychobiological stress. Sixty healthy participants provided data for the analyses. Using an ecological momentary assessment design, participants received 6 prompts on their smartphone for 4 days. At each prompt, they reported on social interactions since the last prompt (any occurrence, frequency, duration, quality, and perceived social support), current subjective stress, and provided one saliva sample for the analyses of cortisol (sCort) and alpha-amylase (sAA). Experiencing any contact within days as well as higher daily levels of contact quality and perceived social support were associated with reduced levels of sCort. Furthermore, on a daily level, experiencing at least one contact in-between prompts more often as well as having more contacts on average attenuated the sAA output. Perceived social support and contact quality as well as higher daily contact durations were associated with lower subjective stress. For sCort, daily levels of stress moderated the effects of experiencing any contact within days while daily perceived social support moderated the effects of subjective stress. For sAA, experiencing at least one contact in-between prompts more often on a daily level moderated the effects of subjective stress. There were no between-person effects throughout all analyses. The results show ecologically valid evidence for direct attenuating effects of social interactions on psychobiological stress as well as for the stress-buffering hypothesis in everyday life. Increasing the quantity and improving the valence of social interactions on an intrapersonal level can possibly reduce psychobiological stress and prevent its consequences.